High Internal Quantum Efficiency AlGaN Epilayer Grown by Molecular Beam Epitaxy on Si Substrate. (7th July 2021) - Yin, Xue; Zhao, Songrui
Abstract : We report the molecular beam epitaxy growth and characterization of aluminum gallium nitride (AlGaN) epilayer on an Si substrate. The AlGaN epilayer was grown on an AlN buffer layer through a coalescence process on a nanowire template. The AlGaN epilayer possessed a relatively smooth surface. The room-temperature internal quantum efficiency (IQE) was investigated using power-dependent photoluminescence experiments and theoretical analysis. A maximum IQE of around 50% is derived, with an estimated carrier density of 3 × 10 18 cm −3 . This IQE is significantly improved compared to the previously reported bulk AlGaN epilayers grown on sapphire and/or AlN-on-sapphire templates. The efficiency droop mechanism is also discussed, which could presumably be attributed to the carrier delocalization.